Characteristics of Morphological Indices of Students with Different Types of Posture - Vypasniak, Igor; Shankovsky, Andriy (Journal of Education, Health and Sport, 2017)
Topicality. Recently, the state of health of students has become the subject of close attention of specialists. Numerous studies conducted in recent years suggest that functional posture impairment is one of the most common abnormalities in the musculoskeletal system of modern students. Research Objectives: to determine the morphological characteristics of students with different types of posture. Research Results. During the experiment, it was found that 74% of the students participating in the research had functional posture impairment, with the largest number among them being students with scoliostic posture. It was found that the number of students with normal posture decreased while the number of functional disorders increased taking into consideration the results of the investigation of different posture types of students of the 1st and the 4th courses of study. The morphological changes of students during the study at the higher educational establishment are determined, and changes in the mass and the circumferential dimensions of the body determine the condition and function of the musculoskeletal system, especially the functional state of the muscular system. Conclusions. The determination of morphological indices of students with different types of posture is the basis for the development of corrective and preventive measures in the process of physical education.